An Experimental Study on the Basic Mechanical Properties and Compression Size Effect of Rubber Concrete with Different Substitution Rates - Yanli Hu; Xuewei Sun; Aiqun Ma; Peiwei Gao (Advances in Civil Engineering)
An experimental study was carried out on the uniaxial compression, uniaxial splitting, pure shear, and compression size effect of rubber concrete with 5 different substitution rates by applying hydraulic servo and direct shear apparatus. Then, by comparing the failure modes and ultimate strength eigenvalues of rubber concrete under different loading conditions, the following conclusions were drawn: with the increase of rubber substitution rate, the concrete specimens maintain a relatively good integrity under uniaxial compressive failure; on the contrary, the failure sections under uniaxial slitting and pure shear gradually become uneven with an increasing amount of fallen rubber particles. With the increase of specimen size, the integrity of rubber concrete after failure is gradually improved. Affected by an increased rubber substitution rate, the uniaxial compressive strength, splitting tensile strength, and shear strength of the concrete gradually decrease, while the plastic deformation capacity gradually increases. Specifically, the compressive strength is reduced by a maximum of 60.67%; the shear strength is reduced by a maximum of 49.85%; and the uniaxial splitting strength is reduced by a maximum of 58.38%. Then, we analyzed the strength relationship and the underlying mechanism among the three types of loading modes. It is found that, at the same rubber substitution rate, the compressive strength of rubber concrete gradually increases as the specimen size decreases, and the size effect on the compressive strength gradually decreases as the rubber substitution rate increases. Meanwhile, we performed qualitative and quantitative analysis on the equation describing the coupling effect of specimen size and rubber substitution rate on the compressive strength; the results suggest that the proposed equation is of a high level of applicability. Our research has a reference value for the application and promotion of rubber concrete in actual engineering projects.